Sobre a transgressão: uma análise semiótica da obra lavoura arcaica, de Raduan Nassar - Vieira Sobrinho, Raquel (2017)
This work aims to investigate the phenomenon of transgression in the novel Ancient Tillage, of the author Raduan Nassar, based on the theory of Discursive Semiotics. We start from the assumption that transgression is constructed in the discourse as a complex modal configuration founded on the opposition between a system of social values and a system of individual values, culminating in the breaking of the implicit fiduciary contract between the subject and his social environment (GREIMAS, 1975). As a consequence of the breach of the contract, the subject whose conduct is not within the expected, according to the current value system, is a transgressor subject to whom a place of marginality can be destined. It is our purpose to describe, based especially on the modalities of having-to, wanting, being-able-to and knowing, how the transgression is a result of those modal categories articulated. Therefore, it is possible to analyze the narrative of the subjects and thus to identify the controversial or contractual relations that are established between them and that appeared in the discourse as family, religious, sexual, etc. conflicts. Finally, we try to show that transgression is a global effect of meaning that goes through the text as a complex modal configuration, involving the conflictual interaction between the modal instances of having-to (a system of social norms), of wanting (dimension of desire), of being-able-to, of knowing and, ultimately, of believing.